(untitled) (Journal of Laboratory Animal Science, 2018)
Sentinel animal testing plays a pivotal role in management of any modern vivarium. It is an extremely useful tool to assess the microbial status of the laboratory animals as part of the comprehensive animal care program. Sentinels pick up the early infection if any, in the micro and/or macro environment, as these animals are placed in a similar environment intentionally. Sentinels are representative animals, independent of the research colonies and are maintained only for the purpose of screening the pathogenic organisms at regular intervals. At times, as part of 3R’s, we have on occasion used research animals to confirm our sentinel results. Sentinel program is concerned with prompt detection of pathogens and the measures to deal with them thereby ensuring the health status of the resident colony. With an effective sentinel monitoring program preventive measures can be taken to enact either, treat, contain or eradicate the pathogen. This review provides insights into the sentinel program with respect to disease surveillance of laboratory animals and conveys why it is necessary for effective in laboratory animal program management